Clovis Stone Tools from El Fin del Mundo, Sonora, Mexico: Site Use and Associations between Localities. Issue 3 (July 2022) - Sánchez-Morales, Ismael; Sanchez, Guadalupe; Holliday, Vance T.
Abstract : El Fin del Mundo is an archaeological site in Sonora, northwest Mexico, that contains a buried Clovis megafauna kill in a lowland area and concentrations of Clovis and later lithic materials scattered on the deflated surface of the surrounding uplands. The Clovis lithic assemblage from the site, identified by its technological and typological features, has been classified into three modes: bifaces, unifaces, and blades. The kill locality only contains Clovis points, whereas the assemblage from the uplands includes multiple bifaces reflecting diverse stages of the manufacture process from blank production to finished, highly reduced, and discarded broken Clovis points, numerous end scrapers, and blades and blade manufacture byproducts. This assemblage is indicative of a campsite where stone tool production and possibly other domestic tasks took place. In addition, a rhyolite outcrop near both the campsite and the kill was intensively exploited, as reflected in the high proportion of this raw material in the Clovis assemblage. Unequivocal association of the kill locality and the campsite is not confirmed; however, the configuration of the site indicates that the campsite was established in uplands near locations with water, game, and lithic resources.